Metode Pemahaman Hadis Ulama Mutaqaddimīn (Tinjauan terhadap Metode Pemahaman Ahli Hadis dan Fuqahā’) - Hasanuddin Sinaga (Refleksi: Jurnal Kajian Agama dan Filsafat, 2019)
Factually, in practicing the word of God can’t be separated from the explanation or explanation of the hadith, because the Prophet did give the task and authority to give an explanation. Explanations and Answers from the Prophet. In discussions with the method of understanding the hadith, so far there are two models of flow, namely the flow of hadith experts (muḥaddithīn) and ra'yi (fuqahā’) experts. Both of these schools have different understanding methods for each other that need knowledge about them which is something that is very important and valuable.